Development of an electron paramagnetic resonance methodology for studying the photo-generation of reactive species in semiconductor nano-particle assembled films. (18th June 2018) - Twardoch, Marek; Messai, Youcef; Vileno, Bertrand; Hoarau, Yannick; Mekki, Djamel E.; Felix, Olivier; Turek, Philippe; Weiss, Jean; Decher, Gero; Martel, David
ABSTRACT: An experimental approach involving electron paramagnetic resonance is proposed for studying photo-generated reactive species in semiconductor nano-particle-based films deposited on the internal wall of glass capillaries. This methodology is applied here to nano-TiO2 and allows a semi-quantitative analysis of the kinetic evolutions of radical production using a spin scavenger probe. Abstract :